Respon Pertumbuhan Bibit Gmelina Arborea Roxb. Terhadap Perlakuan Media Tanam dan Biostimulan di Persemaian Permanen IPB - Johan Ariando Rajagukguk; Yadi Setiadi; Iwan Hilwan; Noor Faiqoh Mardatin (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Nursery activities were one important step in producing quality seedling. This study used a very low quality Gmelina seed with germination value of 9.8%. This value affected the ability of plants in responding to treatment. Input technology of growing media treatment and biostimulan needed to improve the quality of seedling. Sample of media planting collected from IPB permanent nursery. Applications biostimulan was using to help increased amount of plant roots. This study used a completely randomized factorial design with 7 replications. Observations for 8 weeks after planting (MST) found the media's treatment plant and biostimulan has significant effect on the parameters of diameter, height and total dry weight compared to control. Compost was the best medium in this study who had the highest NPK value compared to other media. Biostimulan concentration of 4% was proved improving the quality of Gmelina seedling in all media by increased the compactness of the roots of seedlings. The percentage increased in root dry weight (BKA), the largest found in the media mix of compost and mud. The best treatment in improving the quality of seeds Gmelina found in compost media and biostimulan 4% on all parameters of growth.Keywords: biostimulant, root compaction, seedling quality